South by Southeast - Oddo, Emilia (Archaeopress, 2022)
Contributions investigate the settlement patterns, maritime connectivity, and material culture of the southeast of Crete in a diachronic fashion, in an attempt to define it as a region and trace its history. Papers focus primarily on the archaeology of the sites along the coastal strip spanning between the Myrtos Valley and Kato Zakros.